Assessment of Natural Regeneration Potential of Native Tree Species in a Community Managed Forest of Bangladesh - Jannat, Morgubatul; Kamruzzaman, Md.; Kamal Hossain, Mohammed (International Journal of Environment, 2020)
The study was conducted to explore natural regeneration potential of a community managed forest. Village Common Forest (VCF) has been managed as a commo n property resource under the leadership of Mouza Headmen based on traditional resource management pattern. Stratified random sampling method was carried out for the inventory of the regeneration status. The sampling plot size for regeneration was 5m × 5m. About 47 regenerating tree species belonging to 22 families were recorded from the studied village common forest where Grewia nervosa was the dominant regenerated seedlings. Euphorbiaceae was the dominant family with 7 species followed by Moraceae (5 species), Rubiaceae (4 species), Anacardiaceae (3 species), Combretaceae (3 species) and Mimosaceae (3 species). Maximum Importance Value Index (IVI) was found for Grewia nervosa (27.97) followed by Brownlowia elata (21.52), Artocarpus chama (14.74) and Leea macrophylla (12.53). A total of 78% of the regenerating tree species were regenerated from seeds and 22% from coppices. Shannon-Wiener’s Diversity Index was found 3.37 where Simpson’s Diversity Index was 0.055, Moreover, Margalef’s Richness Index was calculated as 8.57 and Species Evenness Index was 0.88. The results depict that the regeneration status of studied VCF has been satisfactory and Village Common Forest still contains dense forests that represents rich biodiversity including rare species. The study might be helpful for increasing conservation importance of this forest. This study suggests further study on vegetation structure and carbon pool assessment to understand more about of this forest for future sustainability.